Telemedicine delivery of patient education in remote Ontario communities: feasibility of an Advanced Clinician Practitioner in Arthritis Care (ACPAC)-led inflammatory arthritis education program - Warmington K (Dove Medical Press, 2017)
Kelly Warmington,1 Carol Flewelling,2 Carol A Kennedy,3,4 Rachel Shupak,5 Angelo Papachristos,5 Caroline Jones,5 Denise Linton,3 Dorcas E Beaton,3,4,6–8 Sydney Lineker9 1Learning Institute, The Hospital for Sick Children, 2Telemedicine Program, 3Musculoskeletal Health & Outcomes Research, St. Michael’s Hospital, 4Institute for Work & Health, 5Martin Family Centre for Arthritis Care & Research, St. Michael’s Hospital, 6Graduate Department of Health Policy, Management and Evaluation, 7Graduate Department of Rehabilitation Science, 8Department of Occupational Science and Occupational Therapy, University of Toronto, 9The Arthritis Society (Ontario Division), Toronto, ON, Canada Objective: Telemedicine-based approaches to health care service delivery improve access to care. It was recognized that adults with inflammatory arthritis (IA) living in remote areas had limited access to patient education and could benefit from the 1-day Prescription for Education (RxEd) program. The program was delivered by extended role practitioners with advanced training in arthritis care. Normally offered at one urban center, RxEd was adapted for videoconference delivery through two educator development workshops that addressed telemedicine and adult education best practices. This study explores the feasibility of and participant satisfaction with telemedicine delivery of the RxEd program in remote communities.Materials and methods: Participants included adults with IA attending the RxEd program at one of six rural sites. They completed post-course program evaluations and follow-up interviews. Educators provided post-course feedback to identify program improvements that were later implemented.Results: In total, 123 people (36 in-person and 87 remote, across 6 sites) participated, attending one of three RxEd sessions. Remote participants were satisfied with the quality of the videoconference (% agree/strongly agree): could hear the presenter (92.9%) and discussion between sites (82.4%); could see who was speaking at other remote sites (85.7%); could see the slides (95.3%); and interaction between sites adequately facilitated (94.0%). Educator and participant feedback were consistent. Suggested improvements included: use of two screens (speaker and slides); frontal camera angles; equal interaction with remote sites; and slide modifications to improve the readability on screen. Interview data included similar constructive feedback but highlighted the educational and social benefits of the program, which participants noted would have been inaccessible if not offered via telemedicine.Conclusion: Study findings confirm the feasibility of delivering the RxEd program to remote communities by using telemedicine. Future research with a focus on the sustainability of this and other models of technology-supported patient education for adults with IA across Ontario is warranted. Keywords: rheumatoid arthritis, feasibility, patient satisfaction, telehealth, tele-education